2014
DOI: 10.1097/rli.0000000000000031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intrarenal Oxygenation in Iodinated Contrast-Induced Acute Kidney Injury–Susceptible Rats by Blood Oxygen Level–Dependent Magnetic Resonance Imaging

Abstract: Objectives The objectives of this study were to evaluate differences in intrarenal oxygenation as assessed by blood oxygen level–dependent (BOLD) magnetic resonance imaging in contrast-induced acute kidney injury (CIAKI)–susceptible rats when using 4 contrast media with different physicochemical properties and to demonstrate the feasibility of acquiring urinary neutrophil gelatinase–associated lipocalin (NGAL) levels as a marker of CIAKI in this model. Materials and Methods Our institutional animal care and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…Our results using BOLD MRI suggest that residual accumulation of deoxyhemoglobin after contrast imaging can persist for at least 24-27 h and extend results observed in experimental rat models that demonstrate renal hypoxia measured by BOLD MRI after injection of iodinated contrast [37]. Studies in the rat suggest that these changes were associated with AKI as measured by NGAL levels [38]. However, another study from the same authors reported that AKI after renal hypoxia in rats after contrast injection did not occur when the rats were pretreated with furosemide [39].…”
Section: O R I G I N a L A R T I C L Esupporting
confidence: 64%
“…Our results using BOLD MRI suggest that residual accumulation of deoxyhemoglobin after contrast imaging can persist for at least 24-27 h and extend results observed in experimental rat models that demonstrate renal hypoxia measured by BOLD MRI after injection of iodinated contrast [37]. Studies in the rat suggest that these changes were associated with AKI as measured by NGAL levels [38]. However, another study from the same authors reported that AKI after renal hypoxia in rats after contrast injection did not occur when the rats were pretreated with furosemide [39].…”
Section: O R I G I N a L A R T I C L Esupporting
confidence: 64%
“…It has also been used to study changes in renal blood flow associated with CKD and hypertension 106108 . Despite the utility of BOLD MRI in studying renal oxygenation and function in animal models of AKI 109,110 , one recent study evaluating BOLD MRI in the evaluation of AKI in humans found no correlation between MRI findings and GFR 111 . Another recently developed MRI technique known as diffusion-weighted imaging (DWI) detects the motion of water molecules within tissue, and has been used to assess renal fibrosis in both AKI and CKD 81 .…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…risk of acute renal injury after stresses such as the intravenous administration of an iodinated contrast agent (120)(121)(122).…”
Section: S191mentioning
confidence: 99%